2020
DOI: 10.3389/fphys.2020.00298
|View full text |Cite|
|
Sign up to set email alerts
|

Current Knowledge on the Vascular Effects of Menthol

Abstract: Menthol is a monoterpene alcohol, widely used in several food and healthcare products for its particular odor and flavor. For some decades, menthol has been known to act on the vasculature directly in the endothelium and vascular smooth muscle, with recent studies showing that it also evokes an indirect vascular response via sensory fibers. The mechanisms underlying menthol's vascular action are complex due to the diversity of cellular targets, to the interplay between signaling pathways and to the variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…Among strongly activated functions, we can note that the phytogen did not increase the predisposition to any of the diseases; on the contrary, it enhanced a range of beneficial functions such as angiogenesis and vasculogenesis, homeostasis, engulfment of tumour cells, the function of muscle and autophagy to name a few (Supplementary data) while inhibiting non-desirable functions like dysglycemia (abnormalities in blood glucose levels), morbidity and mortality, disorders of blood pressure and more. Vasculogenesis and other cardiovascular beneficial functions enhanced by phytogen are in agreement with previously reported cardioprotective effects of phytogens main ingredients menthol and carvacrol [ 7 , 36 ]. Reduction in mortality related functions is in agreement with our trial data showing consistently reduced mortality in phytogen shed from the second week of phytogen administration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among strongly activated functions, we can note that the phytogen did not increase the predisposition to any of the diseases; on the contrary, it enhanced a range of beneficial functions such as angiogenesis and vasculogenesis, homeostasis, engulfment of tumour cells, the function of muscle and autophagy to name a few (Supplementary data) while inhibiting non-desirable functions like dysglycemia (abnormalities in blood glucose levels), morbidity and mortality, disorders of blood pressure and more. Vasculogenesis and other cardiovascular beneficial functions enhanced by phytogen are in agreement with previously reported cardioprotective effects of phytogens main ingredients menthol and carvacrol [ 7 , 36 ]. Reduction in mortality related functions is in agreement with our trial data showing consistently reduced mortality in phytogen shed from the second week of phytogen administration.…”
Section: Discussionsupporting
confidence: 91%
“…The Qiagen's Ingenuity Pathway Analysis (IPA) is based on over 10 million manually curated gene expression annotations in the Ingenuity Knowledge Base (IKB) [ 60 ] commercial database [ 7 ]. IPA was performed to identify significantly altered pathways ( P < 0.01) and to differentiate if the pathways are activated (positive z -score) or inhibited (negative z-score).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bridging of Western and traditional Chinese medicine has been described as shifting compensatory homeostasis to overall human body homeostasis, in line with the self-healing idea, 83 and among older Chinese adults, the use of traditional Chinese medicine has been shown to be effective, although there are some conflicting results. 84 , 85 For example, menthol acts on vasculature directly in the vascular smooth muscle and endothelium and recent studies have shown that it causes an indirect vascular response via sensory fibers 86 and menthol gel can acutely reduce pain intensity. 87 Cold therapy can reduce edema in acute situations; vasoconstriction occurs both in response to reflex and local cooling of the skin; however, patients should be aware than cooling longer than 20 minutes can be harmful as a sudden switch to vasodilation can be triggered (hunting reaction).…”
Section: Integrative Medicine Within the Self-healing Conceptmentioning
confidence: 99%
“…Recent research suggests that the Mentha x villosa species has a hypotensive effect through bradycardia and vasodilation [ 115 ]. Although several mint substances may display this vasoactive effect, it has definitely been detected in menthol [ 116 ].…”
Section: Medical Applicationsmentioning
confidence: 99%